A fluorescent film sensor for high‐performance detection of Listeria monocytogenes via vapor sampling. Issue 1 (28th April 2022) - Huang, Rongrong; Li, Meiqi; Lin, Dehui; Shao, Yangtao; Shang, Congdi; Liu, Qianqian; Liu, Guijun; Li, Nan; Miao, Rong; Peng, Haonan; Tang, Yanli; Fang, Yu
Abstract: Foodborne Listeria monocytogenes poses serious threats to public health. Fast and sensitive detection of the pathogen at the point of contamination is thus crucial to halt the spread of bacteria‐related diseases. Herein, we report for the first time a fluorescent film sensor to detect the biomarker of L. monocytogenes, 3‐hydroxy‐2‐butanone. The sensor demonstrated unprecedented sensing performance for the analyte with a detection limit lower than 0.05 mg/m 3, response time less than 1 s, full reversibility, and excellent selectivity. Further study showed that the sensor can be used to monitor the growth of L. monocytogenes with much‐improved sensitivity. The superior performance of the sensor is ascribed to the specific binding, efficient charge transfer emission, and porous adlayer structure of the specially designed sensing fluorophore‐based film. Our work paves the way to develop a portable detector to meet the needs for on‐site and real‐time detection of foodborne pathogens. Abstract : A newly designed AIEgen‐based fluorescent film sensor is developed and used successfully, for the first time, to detect gaseous 3‐hydroxy‐2‐butanone, a biomarker of Listeria monocytogenes . The sensor depicts fast, sensitive, selective, and fully reversible sensing performance toward the analyte, as evidenced by the reliable finding of the foodborne pathogen at the very early stage.